Norms, institutions and freedom of speech in the US, the UK and Australia - Gelber, Katharine (Journal of public policy, 2021)
While it has become accepted that norms can act in institution-like ways, a highly valued norm that has not been examined is free speech. Can free speech be conceptualised as acting in institution-like ways? If it can, what does this illuminate about processes of policy change? I analyse policy change between 2001 and 2011 in the United States, the United Kingdom and Australia, a period during which significant new limits were introduced on free speech in relation to national security. In addition to showing how free speech acted in institution-like ways, the analysis suggests three implications: norms can both act in institution-like ways and be subject to change in interaction with other institutions; a broad, cultural level institution can mask policy change at the narrow, rule-based level even where the latter contradicts the former; and complexity and variation in speech regulation can be understood as consequences of the to-be-expected variability in the institutionalisation of a norm.